2021
DOI: 10.3389/fcimb.2021.734296
|View full text |Cite
|
Sign up to set email alerts
|

Altered Pseudomonas Strategies to Inhibit Surface Aspergillus Colonies

Abstract: Pseudomonas aeruginosa and Aspergillus fumigatus infections frequently co-localize in lungs of immunocompromised patients and individuals with cystic fibrosis (CF). The antifungal activity of P. aeruginosa has been described for its filtrates. Pyoverdine and pyocyanin are the principal antifungal P. aeruginosa molecules active against A. fumigatus biofilm metabolism present in iron-limited or iron-replete planktonic P. aeruginosa culture filtrates, respectively. Using various P. aeruginosa laboratory wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…These data suggest that pyoverdine is not solely responsible for combined anti-fungal activity of filtrates and VCZ, and that different amounts of one or more other factors are present in filtrates that interact with VCZ. We studied rhamnolipid production ( Sass et al., 2021 ), and found that isolates 14-82 and 14-119 were capable of producing rhamnolipids, whereas isolates 14-89 and 14-116 were not. This ability to produce rhamnolipids correlated with their abilities to interact synergistically with VCZ at high dilutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that pyoverdine is not solely responsible for combined anti-fungal activity of filtrates and VCZ, and that different amounts of one or more other factors are present in filtrates that interact with VCZ. We studied rhamnolipid production ( Sass et al., 2021 ), and found that isolates 14-82 and 14-119 were capable of producing rhamnolipids, whereas isolates 14-89 and 14-116 were not. This ability to produce rhamnolipids correlated with their abilities to interact synergistically with VCZ at high dilutions.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas competes with Aspergillus for crucial resources, e.g., iron, via a variety of their products, such as phenazines, its major siderophore pyoverdine ( Sass et al., 2017 ), pyocyanin (5-N-methyl-1-hydroxyphenazine) ( Kerr et al., 1999 ; Briard et al., 2015 ; Sass et al., 2020 ), 1-hydroxyphenazine ( Kerr et al., 1999 ; Briard et al., 2015 ), phenazine-1-carboxamide ( Briard et al., 2015 ), phenazine-1-carboxylic acid ( Briard et al., 2015 ), and rhamnolipids ( Briard et al., 2017 ; Sass et al., 2021 ). Using laboratory reference isolates (PA14, PAO1) we recently showed that the Pseudomonas products pyoverdine, pyocyanin, and pyochelin interacted synergistically with the anti-fungal drug VCZ against A. fumigatus forming biofilm in vitro ( Sass et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are necessary in order to better understand the different phenomena detected in both researches, but we can raise some hypotheses: (i) the concentration of pyoverdine could interfere with the outcome of fungal growth, since this bioactive molecule can present both inductive or inhibitory effects on A. fumigatus depending on its concentration [49]; (ii) in the Le Govic and co-workers study [54], the effect of pyoverdine was evaluated with the purified molecule, whereas we utilized a pool of molecules secreted by P. aeruginosa, so the function of one molecule could interfere with the activity of another; and (iii) the culture media (SCFM versus potato dextrose agar) utilized in each work, besides the difference between the growth and molecule diffusion in liquid and solid media, could also interfere in pyoverdine production. Accordingly, in a study performed with A. fumigatus, it was determined that the major antifungal molecules produced by P. aeruginosa in liquid medium (siderophores) differ from those produced on solid media (rhamnolipids and elastase) [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the manner in which the P. aeruginosa QS system plays an essential role in interfering with the growth of A. fumigatus [131,132,192]. The QS system enables bacteria to enhance their pathogenicity, including migration and biofilm formation.…”
Section: Cystic Fibrosis (Cf)mentioning
confidence: 99%